2019
DOI: 10.1111/deci.12355
|View full text |Cite
|
Sign up to set email alerts
|

How to Find the Right Supply Chain Strategy? An Analysis of Contingency Variables

Abstract: Contingency variables are characteristics of the business environment that influence the competitive priorities supply chains should pursue for maximizing profits. But which contingency variables should managers focus on when developing a supply chain strategy? On the one hand, if important variables are omitted, the selected strategy may fail to fulfill the needs of the business environment. On the other hand, considering irrelevant variables unnecessarily complicates the strategy formation process, hence pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 60 publications
0
15
0
Order By: Relevance
“…Furthermore, the value density of the product (i.e. unit value/volume or weight) is traditionally used in logistics to assess the impact of transportation costs on sales profitability (von Falkenhausen et al, 2019;Gevaers et al, 2011;Lovell et al, 2005;Cooper, 1993).…”
Section: Reference Framework and Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the value density of the product (i.e. unit value/volume or weight) is traditionally used in logistics to assess the impact of transportation costs on sales profitability (von Falkenhausen et al, 2019;Gevaers et al, 2011;Lovell et al, 2005;Cooper, 1993).…”
Section: Reference Framework and Methodologymentioning
confidence: 99%
“…Such an achievement becomes a must when companies deliver goods with a low value density, i.e. with a low unit value and a high volume/weight (Cooper, 1993;Gevaers et al, 2011;Lovell et al, 2005;Von Falkenhausen et al, 2019). This discussion is leading scholars and managers to think about the kind of logistic service that can be offered under reasonable conditions of efficiency, while still providing the client with good levels of speed, dependability, and availability of products for digital purchases.…”
Section: Supply Chain Management Perspectivementioning
confidence: 99%
“…Studies have investigated various resilience approaches used to avoid or minimize the damages brought on by natural disasters. Such approaches include cultivating redundant supply sources (Silbermayr and Minner, 2014), maintaining reserve inventory (Morrice et al, 2016), developing a business/ disaster recovery plan (Sahebjamnia et al, 2018;Karakasidis, 1997) that includes contingencies in supply chain strategy (Von Falkenhausen et al, 2019) and strategic partnering (Ojha et al, 2014). In particular, Ojha et al (2013) found support for a positive relationship between financial performance and logistical business continuity planning mediated by DI.…”
Section: 12mentioning
confidence: 99%
“…The increase in the product variety tends to produce a negative impact on the level of services (Closs et al , 2010; Falkenhausen et al , 2019), setup times (Er and MacCarthy, 2006) and operational costs (Thonemann and Bradley, 2002), as the internal, organizational and structural complexities of the supply chain increase and thereby decrease operational performance (Bozarth et al , 2009). On the other hand, some authors claim that it is possible to increase variety without affecting the fill rate.…”
Section: Literature Reviewmentioning
confidence: 99%